Manajemen Proyek Rancang Bangun Aplikasi E-Commerce Berbasis Website Untuk Batik Khas Tangerang - Agung Wijoyo; Bangun Suprianto; Irfan Alamsah; Jepri Afrizal; Khoiriyah; Wike Rahayu (CV. Multi Kreasi Media, 2024)
Project management is the art and science of planning and guiding projects to achieve predetermined goals. In project management, many constraints arise which can result in lengthy development and system development. This research discusses the creation of a website-based e-commerce application design for Tangerang typical batik at CV Ladang Emas Productions, which aims to get an overview of designing a digital goods sales system, the problems that arise and how to design an efficient e-commerce application system. according to the elements of the problem in the shop. The problem is that CV Ladang Emas Productions, in managing and conducting sales transactions of goods in the form of typical Tangerang batik clothing, still uses a manual system. This can be seen from the preparation of reports and the management of sales of goods which are still not systematic. The website-based e-commerce application system is a new system offer that is expected to be a solution in solving problems. With the existence of a website-based e-commerce application system, it is hoped that it will be able to make batik clothing sales transactions systematically, produce accurate sales information, and make reporting easier.